(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Majority of patients visiting Ayurvedic hospitals are having ailments related to joints especially low back pain and knee joint pain. Low back ache may be due to many reasons ranges from muscular pain to complicated neurological complaints or malignancy. Disc herniation is also a major reason for low back ache in which radiculopathy might be a typical feature. In all systems of medicine many treatments exist to manage low back ache and sciatica. In Ayurveda also different treatment modalities are present ranging from simple internal medications to complex therapies like Basti (therapeutic enema), to effectively tackle such conditions. The Ayurvedic formulation, Rasna guggulu is mentioned in the treatment of Gridrasi (sciatica). To standardize any formulation its properties should be studied repeatedly in detail. Even though this formulation is comparatively a simpler one consisting of only 3 ingredients, its properties and identifying features are not widely studied. In this study pharmacognostical, organoleptic and physico-chemical characteristics of Rasna guggulu were reported. Pharmacognostical study of this drug reveals the presence of epidermal cells, starch grain, lignified stone cells, prismatic crystals, simple fiber, simple trichome, warty trichome, annular vessels and spiral vessels of Rasna along with oil globules of clarified butter. HPTLC shows 8 and 7 spots at 254nm and 366nm respectively which suggests the presence of 7 – 8 active principles in this drug. This study also can be considered to standardize the formulation, Rasna guggulu.